1997
DOI: 10.1073/pnas.94.11.5703
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Pax2 and Pax5 in midbrain and cerebellum development

Abstract: Midbrain and cerebellum development depends on an organizing center that is located at the midbrainhindbrain junction of the vertebrate embryo. Expression of the two closely related transcription factors Pax2 and Pax5 overlaps spatially and temporally in this region of the developing central nervous system. To study a possible interaction of these transcription factors in midbrain and cerebellum patterning, we have generated Pax5, Krd double mutant mice. The transgene-induced Krd mutation corresponds to an Ϸ7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(83 citation statements)
references
References 49 publications
(81 reference statements)
5
76
1
1
Order By: Relevance
“…9 In addition to its expression in B cells, PAX5 protein and/or mRNA has been reported to be expressed in normal and neoplastic cell types in the central nervous system, testis and bladder. 3,[10][11][12][13][14][15] B-cell malignancies may express PAX5 in the absence of expression of other pan-B-cell markers, suggesting that the inclusion of PAX5 in a panel of antibodies to assess undifferentiated malignant neoplasms may have diagnostic benefit. To address this possibility, we studied examples previously diagnosed as undifferentiated malignant neoplasms for PAX5 expression by immunohistologic methods.…”
mentioning
confidence: 99%
“…9 In addition to its expression in B cells, PAX5 protein and/or mRNA has been reported to be expressed in normal and neoplastic cell types in the central nervous system, testis and bladder. 3,[10][11][12][13][14][15] B-cell malignancies may express PAX5 in the absence of expression of other pan-B-cell markers, suggesting that the inclusion of PAX5 in a panel of antibodies to assess undifferentiated malignant neoplasms may have diagnostic benefit. To address this possibility, we studied examples previously diagnosed as undifferentiated malignant neoplasms for PAX5 expression by immunohistologic methods.…”
mentioning
confidence: 99%
“…Several experimental animal studies have suggested that initiation and functioning of this organising centre crucially depends on Pax2 [1,16,22,23], and that the regulatory role of Pax2 is an evolutionarily conserved feature for all vertebrates [14]. Furthermore, it has been shown that a mutation of the Pax2 gene in the isthmus leads to the loss of the midbrain and the cerebellum [3,15,22].…”
Section: Discussionmentioning
confidence: 99%
“…В экспериментах с костным мозгом PAX-5 -/-мышей дифференцировка В-клеток останав-ливалась на стадии ранних про-В-клеток [53]. В зависимости от окружения (ростовых факто-ров, стромальных клеток костного мозга) PAX-5 -/-клетки in vitro могут сохранять возможность дифференцировки в разные клетки миелоидно-го и лимфоидного ростков, а при восстановле-нии экспрессии PAX-5 -вновь ограничиваются в возможности развития только в направлении В-лимфоцитов [37].…”
Section: роль Pax-5 в развитии в-лимфоцитовunclassified